Pengembangan Sistem Informasi Praktik Kerja Industri (Prakerin) Menggunakan V-Model Studi Kasus: SMKN 2 Malang - Mochamad Bachtiyar Eko Cahyo Putro; Ahmad Afif Supianto; Djoko Pramono (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Malang State Vocational High School 2 every year carries out industrial work practices (internship). In the internship activities, the school has difficulty, because the industrial work practice data management process was managed manually. This resulted in several difficulties, one of which was in the registration of apprenticeship, the head of the department had difficulty recording data for all students who enroll in apprenticeship, because the head of the department needed to visit classes according to his department to provide a list of Business / Industrial World that can be chosen by students., then the head of the department needs to record the data of the students and where students want to carry out internship. Based on these problems, a web-based Prakerin Information System was built. In the system development process, the SDLC method will be used is V-model. The results of the requirements analysis are strongly approved by the user, evidenced by the results of User Acceptance Testing (UAT), with a system that can run in accordance with the expected system functionality as evidenced by system testing. The system is implemented using the PHP programming language and MySQL database management system. Implementation of the system is in accordance with the results of the design made, because the results of unit testing are all sample functions in accordance with the flow of design sequence diagrams and the system has a well structured and written code, high testability, and less cost and effort, then integration testing produces a valid percentage of 100% which means the system has been well integrated.